Promoting evidence-informed policymaking through capacity enhancement in implementation research for health researchers and policymakers in Nigeria: A cross-sectional study - Chigozie Jesse Uneke; Abel Ebeh Ezeoha; Henry Chukwuemeka Uro-Chukwu (Wolters Kluwer Medknow Publications, 2018)
Background: Capacity constraints on implementation research among policymakers and researchers are a major challenge to the evidence to policy link. This study was designed to bring together senior policymakers and researchers in Nigeria to consider issues around research-to-policy interface and enhance their capacity on implementation research. Methods: The design was a cross-sectional study. A 3-day joint implementation research workshop was held for policymakers and researchers using World Health Organization/TDR Implementation Research Toolkit. Assessment of participants' capacity for evidence-informed policymaking and knowledge on implementation research was done using a 5-point Likert scale questionnaire. A postworkshop key informant interview was also conducted. Results: A total of 20 researchers and 15 policymakers participated in the study. The interaction/partnership between policymakers and researchers was generally rare in terms of priority-setting process, involvement as coinvestigators, and executing strategies to support policymakers' use of research findings. The mean ratings (MNRs) recorded mostly ranged from 1.80 to 1.89 on the 5-point scale. Researchers were rarely involved in the generation of policy-relevant research that satisfies policymakers' needs with MNR very low at 1.74. The MNRs for capacity to acquire, assess, and adapt research were generally considerably higher among researchers (3.16-3.82) than policymakers (2.27-3.20). There was a general consensus that the training tremendously improved participants' understanding and use of implementation research. Conclusion: Policymakers and researchers are increasingly recognizing their need to work with each other in the interest of the health systems. There is a need to create more capacity enhancement platforms that will facilitate the interface between them.